Determination of Perfluorooctanoic Acid and Perfluorooctane Sulfonate in Water Samples from Sungai Langat, Malaysia - Zainuddin, Khairunnisa (2010)
Perfluorinated compounds (PFCs) are non-degradable and persistent compounds, bioacculumative and possess toxic characterictics. The compounds are produced in large quantities, applied and disposed without proper monitoring and regulation within the last half-century. If the PFCs productions are to end today, the compounds would continue to persist in the environment for many years to come. Currently in Malaysia there are no studies concerning Perfluorooctanoic acid (PFOA) and Perfluorooctane sulfonate (PFOS) and no regulations has been developed to control these compounds. The method used in this study involves solid phase extraction together with liquid chromatography coupled with mass spectrometry (LC/MS/MS). Results from the water samples taken from Langat River, Malaysia indicated that relatively high concentration of PFOS can be found in the eastern of the river; one of the most populated areas within the basin (station S16 – station S35) with the highest concentration in station S35 (43.5ng/mL). Reason for this is that the compound was highly used in industry as well as in manufacturing processes and consumer products. Relatively high concentration of PFOA can be found in station S6 (5.94 ng/mL) since station S6 is the station receiving effluent from landfill site. Continuous studies on the PFCs compounds could provide more data set and larger view of current state of PFCs contamination in Malaysian aquatic environments.